A SUBJECTIVE FEATURE EXTRACTION FOR SENTIMENT ANALYSIS IN MALAYALAM LANGUAGE - Jisha P. Jayan; Deepu S. Nair AND Elizabeth Sherly (Research Cell : An International Journal of Engineering Sciences, 2015)
In recent days, Sentiment Analysis has become an active research in NLP, which analyzes people's opinions, sentiments, evaluations, attitudes, and emotions from writing language. The growing importance of sentiment analysis coincides with the growth of social media such as reviews, forum discussions, blogs, and social network. In his paper, sentiment analysis of Malayalam film review is carried out using machine learning techniques CRF combined with a rule based approach. The system shows 82 % accuracy.